2022
DOI: 10.24072/pcjournal.103
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of symbiotic bacterial communities in the plant pest Bemisia tabaci reveal high prevalence of Candidatus Hemipteriphilus asiaticus on the African continent

Abstract: Microbial symbionts are widespread in insects and some of them have been associated with adaptive changes. Primary symbionts (P-symbionts) have a nutritional role that allows their hosts to feed on unbalanced diets (plant sap, wood, blood). Most of them have undergone genome reduction, but their genomes still retain genes involved in pathways that are necessary to synthesize the nutrients that their hosts need. However, in some P-symbionts, essential pathways are incomplete and secondary symbionts (S-symbionts… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…This is to show that if there are multiple genetic variants within the population, we might predict that the presence/absence and relative abundance of different haplotypes would show variation among whitefly samples harbouring a particular species of the endosymbiont. Similarly, three strains of Hemipteriphilus were detected in one study on MED Q1 and MED Q3 and ASL whiteflies using three genes including 16S rRNA gene (483 bp), GroEL (269 bp) and GltA (190 bp;Mouton et al, 2022).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…This is to show that if there are multiple genetic variants within the population, we might predict that the presence/absence and relative abundance of different haplotypes would show variation among whitefly samples harbouring a particular species of the endosymbiont. Similarly, three strains of Hemipteriphilus were detected in one study on MED Q1 and MED Q3 and ASL whiteflies using three genes including 16S rRNA gene (483 bp), GroEL (269 bp) and GltA (190 bp;Mouton et al, 2022).…”
Section: Discussionmentioning
confidence: 91%
“…Here, we found that Hemipteriphilus sequences were clustered with one strain of Rickettsia. Another study in Burkina Faso also identified Hemipteriphilus similar to Rickettsia using 16S rRNA gene in Illumina sequencing technology in MED-Q1, MED-Q3 and ASL genetic groups (Mouton et al, 2022). The sequences of Hemipteriphilus and Rickettsia are so similar that they are difficult to differentiate especially using 16S rRNA primers.…”
Section: Discussionmentioning
confidence: 99%
“…Arsenophonus might establish co-obligate symbiotic systems with Portiera in Asia II 6 as well as in T. vaporariorum . In many geographic regions, Hamiltonella and Arsenophonus are rarely found in the same individual of B. tabaci and T. vaporariorum ( 16 23 , 67 ), suggesting that the two symbiotic bacteria are competing over functional and cytological niches. Moreover, it appears that the habitat segregation system was established in a common ancestor of species in Aleyrodinae and was conserved, while the bacterial partners coexisting with Portiera have been replaced ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…That most foreign genes so far reported in eukaryotes are from prokaryotes (this is especially true for insects [31,66]) may in part be due to the capacity of several bacteria to transfer their DNA to eukaryotic cells through conjugation [67]. Furthermore, many arthropod and other metazoan species harbor obligate or facultative intracellular symbionts [68], some of which are in close contact with the host germline genome, facilitating HT [30]. The higher proportion of foreign prokaryotic versus eukaryotic genes so far 9 uncovered in eukaryote genomes may also have methodological underpinnings.…”
Section: How Can Plant Dna Be Transferred To Insects?mentioning
confidence: 99%